The similarity-aware relational division database operator - Gonzaga, André S.; Cordeiro, Robson L. F. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2018: Anais do XXXI Concurso de Teses e Dissertações, 2018)
This paper describes the motivation, contributions and impact of the MSc. dissertation that proposes the first Similarity-aware Division (÷̂) database operator. The novel operator is naturally well suited to answer queries with an idea of “candidate elements and exigencies” to be performed on complex data from real applications of high-impact, such as in agriculture, genetics, industrial production, digital libraries and enterprise management.